Plan de mejora la ruta 69 (2021)
The realization of this project is based on the application proposal of E-commerce, E-business taking into account the various aspects of Branding for the route 69 company. In order to pass this proposal on to the company, it is necessary to show the origin of these two electronic commerce tools (e-commerce), analyze what they are based on, their concept, the innovation they have and the use that companies of the 21st century are giving them; teaching him a great variety of theoretical references and a wide bibliography, which supports the importance and growth of the same, also supporting the proposal. Taking into account that the concepts that the proposal deals with are mainly ICT, Branding, social networks, web pages and emails; mentioning the importance, origin and link they have with respect to online business and commerce tools. Route 69 is a company with incredible recognition among its customers, which has always been characterized by quality, gourmet essence of its products, excellent customer service and optimal human quality; And although they have a fairly good degree of profitability and daily income, the owners are interested in innovating and becoming part of the electronic market, in order to offer their customers the catalog of their products and be able to open a bigger door to have greater communication with your clients and future clients.